The order of completing MDP and D12 does not affect the breathlessness responses: A randomised controlled trial - Wemar, Isabelle; Sandberg, Jacob ; 0000-0003-1863-2033; Olsson, Max ; 0000-0002-0437-3168; Sundh, Josefin; Ekström, Magnus ; 0000-0002-7227-5113 (Chronic Respiratory Disease, 2025)
Background Breathlessness is a common and distressing symptom across a wide range of medical conditions. Different aspects (dimensions) of breathlessness can be assessed using the Multidimensional Dyspnoea Profile (MDP) and Dyspnoea-12 (D12) questionnaires. We aimed to examine whether the order of completing MDP and D12 affects the breathlessness responses in people with cardiorespiratory disease. Methods This was a randomised controlled trial embedded within a longitudinal clinical study. Outpatients with cardiorespiratory disease were randomly assigned to either first complete the MDP or the D12. Primary outcome was mean difference in D12 total score between groups, secondary outcome was mean difference in D12 and MDP subdomain scores. Both outcomes were compared to the minimal clinically important difference (MCID) for each scale. Results All 182 participants from the longitudinal study were included. 93 were randomized to complete MDP first and 89 to D12 first. Characteristics such as age, sex, main cause of breathlessness and smoking status were similar between groups. The mean difference for D12 total score (MCID = 2.8) was −1.5 (−4.2 to 1.3, p = 0.26) between groups. Mean differences between groups in subdomain scores were also below the corresponding MCID. Conclusion The order of completion of MDP and D12 did not impact the scores significantly, but the study lacked power to find smaller yet clinically significant differences. The study supports that the most practical order of completing the instruments can be used in future research and in clinical settings.